The Role of Country Origin and Product Knowledge in Wuling Electric Car Purchase Decision in Indonesia - Ahmad Syaugi Al Gifary; Mahrinasari MS; Nuzul Inas Nabila (PT FORMOSA CENDEKIA GLOBAL, 2024)
In today's competitive marketing landscape, understanding factors influencing consumer purchase decisions is crucial. This study examines the impact of country-of-origin image and product knowledge on the purchasing decisions for Wuling electric vehicles in Indonesia. Employing a descriptive quantitative approach with a sample of 104 respondents, the research uses literature reviews and questionnaires to gather data. Multiple linear regression analysis reveals that both country-of-origin image and product knowledge significantly affect purchasing decisions, with positive coefficients indicating their substantial influence. Specifically, a favorable perception of China's technological advancements and product quality, alongside strong product knowledge, plays a vital role in shaping consumer choices. The findings suggest that Wuling should focus on enhancing its country image and leveraging social media to increase brand awareness. Future research could expand to include additional variables and countries for a broader understanding of purchase decision factors